Interação pontas-adjuvantes na estimativa do risco potencial de deriva de pulverizações - Madureira, Ronaldo P. [UNESP]; Raetano, Carlos G. [UNESP]; Cavalieri, Jhonatan D. [UNESP] (Univ Federal Campina Grande, 2015)
There is increasing concern about the risk of pesticide spray drift and their effects on the environment, becoming increasingly important to use spray technologies that provide greater security. This study aimed to evaluate flat angled fan nozzle and the air induction flat fan nozzle combined to different spray adjuvant for agricultural use to estimate the potential risk of spray drift through deposits and spectrum of drops. The treatments were four spray solutions combined with two spray nozzles. Spray deposits were measured at different distances and heights into a wind tunnel. Indicators of droplet spectrum were: percentage of droplets volume smaller than or equal to 100 mu m of diameter, volume median diameter (VMD), and relative span factor, obtained in a laser particle analyser. The addition of vegetal polymer adjuvant to water resulted in lower levels of spray deposits, reducing the percentage of droplets volume smaller than or equal to 100 mu m of diameter and showed larger VMD, indicating low potential risk of spray drift. Higher deposit levels were obtained under angled flat fan nozzle without addition of adjuvant to the spray solution, which represents a greater potential risk of spray drift.

É crescente a preocupação com os riscos da deriva em pulverizações com produtos fitossanitários e seus efeitos sobre o ambiente, sendo cada vez mais importante a utilização de tecnologias que forneçam maior segurança. Objetivou-se avaliar pontas de pulverização de jato plano inclinado e jato plano com indução de ar empregadas na pulverização com diferentes adjuvantes de uso agrícola na estimativa do risco potencial de deriva por meio dos depósitos e espectro das gotas. Os tratamentos consistiram de quatro soluções combinadas a duas pontas de pulverização. Os depósitos foram medidos em diferentes distâncias e alturas, em túnel de vento. Os indicadores relativos ao espectro de gotas foram: porcentagem do volume de gotas com diâmetro menor ou igual a 100 µm, diâmetro da mediana volumétrica (DMV) e a amplitude relativa, determinados em um medidor de partículas a laser. A adição do adjuvante polímero vegetal à água propiciou diminuição dos depósitos, redução da porcentagem do volume de gotas com diâmetro menor ou igual a 100 µm e DMV maiores, indicando redução do risco potencial de deriva. Depósitos maiores foram obtidos com a ponta de jato plano inclinado sem adição de adjuvantes à calda, representando maior risco potencial de deriva em pulverização.
Interaction spray nozzle-adjuvant to estimate potential risk of spray drift
Keywords: Application technology; Droplet spectrum; Vegetal polymer; Surfactant; Methyl ester